High density lipoprotein cholesterol levels are an independent predictor of the progression of chronic kidney disease. (11th May 2013) - Baragetti, A.; Norata, G. D.; Sarcina, C.; Rastelli, F.; Grigore, L.; Garlaschelli, K.; Uboldi, P.; Baragetti, I.; Pozzi, C.; Catapano, A. L.
Abstract Objectives Patients with chronic kidney disease (CKD) often present with reduced plasma HDL cholesterol (HDL‐C) levels. Whether this reduction in an epiphenomenon or is involved in disease progression is unclear. The aim of this study was to investigate the relation between HDL‐C levels/function and CKD progression in patients with different degrees of disease. Design A total of 176 patients with CKD [glomerular filtration rate (GFR) 50.3 ± 29.1 mL min−1] were recruited and followed for up to 84 months. Lipid profile, metabolic status and kidney function were evaluated at predetermined times. Age‐matched control subjects were selected from the PLIC study (n = 453). Scavenger receptor class B member 1 (SR‐BI) and ATP‐binding cassette transporter A1 (ABCA‐1)‐dependent efflux of cholesterol were measured in CKD patients and in age‐matched control subjects. Results Low HDL‐C levels, diabetes and hypertension were associated with reduced GFR. At follow‐up, low HDL‐C levels were associated with earlier entry in dialysis or doubling of the plasma creatinine level (P = 0.017); HDL‐C levels were the only lipid parameter that affected the progression of CKD (hazard ratio 0.951, 95% confidence interval 0.917–0.986, P = 0.007), independently of the presence of diabetes. Only SR‐BI‐mediated serum cholesterol efflux was significantly reduced in the group of CKD patients with low HDL‐C levels compared to the control group. Conclusions CKD patients with low levels of plasma HDL‐C have a poor prognosis. HDL functionality is also impaired in renal dysfunction. These data support the relevance of HDL in influencing CKD progression.